Demotivating Factors of Indonesian College Students to Learn English as A Foreign Language - Adara, Reza Anggriyashati (Yayasan Sukma, 2018)
Investigating demotivating factors can help teachers to avoid them and provide more insights on sustaining learners’ interest in FL learning. The present study aimed to analyse demotivating factors in FL learning. To obtain the findings, the present study applied a mixed method approach. A set of questionnaires adapted from Sakai and Kikuchi’s (2009) questionnaires were distributed to thirty eight university students whereas interviews were conducted to three of them. The findings indicated teacher’s competence and lack of intrinsic motivation as the most salient factors that caused demotivation among the participants. In this consideration, teachers were perceived as incompetent by the participants when teachers have poor English pronunciation and do not provide communicative classrooms. On the other hand, lack of intrinsic motivation was indicated by the loss of students’ interest in learning and their goal to be an English speaker. Providing a communicative classroom with a fluent teacher as well as promoting students’ interest in English language and culture seem to be the solutions to reduce students’ demotivation. [Penelitian tentang faktor-faktor yang menurunkan motifasi (demotivation) dapat membantu para guru untuk menghindari factor-faktor tersebut dan memberikan wawasan untuk mempertahankan minat peserta didik dalam pembelajaran bahasa asing. Penelitian ini menganalisis faktor demotivasi dalam pembelajaran Bahasa asing. Untuk memperoleh jawaban dari beberapa pertanyaan, penelitian ini menerapkan pendekatan metode campuran. Seperangkat kuesioner yang diadaptasi dari model Sakai dan Kikuchi (2009) didistribusikan kepada tiga puluh delapan mahasiswa sedangkan wawancara dilakukan terhadap tiga dari mahasiswa tersebut. Temuan menunjukkan bahwa kompetensi guru dan kurangnya motivasi intrinsik merupakan faktor yang paling menonjol yang menyebabkan demotivasi di antara para peserta. Dalam hal ini, guru dianggap tidak kompeten oleh para peserta ketika guru memiliki pelafalan bahasa Inggris yang buruk dan tidak menyediakan ruang kelas yang komunikatif. Di sisi lain, kurangnya motivasi intrinsik ditunjukkan oleh hilangnya minat siswa dalam belajar dan tujuan mereka untuk berbicara dalam bahasa Inggris. Menyediakan ruang kelas yang komunikatif dengan guru yang fasih serta mempromosikan minat siswa dalam bahasa dan budaya Inggris tampaknya menjadi solusi untuk mengurangi demotivasi siswa]